Blood Lead Levels in Women of Child-Bearing Age in Sub-Saharan Africa: A Systematic Review - Bede-Ojimadu, Onyinyechi; Amadi, Cecilia Nwadiuto; Orisakwe, Orish Ebere (Frontiers in Public Health, 2018)
This paper reported available studies on blood lead level of childbearing age in sub-Saharan African women. PubMed and Google scholar databases were searched for original articles reporting blood lead levels of women of childbearing age in sub-Saharan Africa. Searches were not limited to year of study but limited to studies published in English Language. Data were extracted and synthesized by estimating the weighted mean of the reported blood lead levels. Fifteen papers fulfilled the inclusion criteria. Mean blood lead levels of women in the studies ranged from 0.83 µg/dl to 99 µg/dl. The overall weighted mean of blood lead levels was 24.73 µg/dl. The weighted mean from analyses of data on blood lead levels of pregnant women alone was 26.24 µg/dl. Identified sources of lead exposure included lead mine, informal lead-acid battery recycling, leaded gasoline and piped water. Elevated BLLs were associated with incidence of preeclampsia, hypertension and malaria. Key factors for elevated blood lead levels (BLL) in these women include poverty, high environmental lead burden and low awareness on lead exposure hazards. BLLs of women of childbearing age in SSA are unacceptably high. There is need therefore, for aggressive programs to address lead exposure in this population.